Phyllodes tumor of right breast with metastasis to lungs, rare presentation - Nichkaode, Prabhat B.; Patel, Sachin Kumar (International Surgery Journal, 2017)
Incidence of Phylloids tumor of the breast is between 0.5% to 2% of all breast tumors. Most common age of occurrence is between 45-49 years but it can occur even at younger age. It is important to distinguish it from more benign tumors of the breast like fibroadenoma as far the management is concerned. Phylloids are fibroepethilial tumors with malignant potential, so needs complete excision. We present a case of 53 years female who underwent simple mastectomy for high grade Phylloids tumor in her right breast a year back, presented with breathlessness and local recurrence, proved to be metastatic Phylloids to lung causing left pleural effusion and nodule in the right upper lobe of lung. When the effusion was tapped it appeared to be pleomorphic spindle cell metastasis.